Role of C reactive protein, hyperbilirubinemia and mean platelet volume in diagnosis of acute appendicitis and its correlation post operatively with histo-pathological examination - Mahendra, Tiwari Sachin; Agrawal, Saurabh (International Surgery Journal, 2023)
Background: Acute appendicitis is one of the most common abdominal emergencies requiring emergency surgery. The diagnosis based on the onset of symptoms and physical examination. Therefore, inaccuracies caused by subjective interpretation are frequent. This raises the need for tests to help diagnose acute appendicitis and predict the severity of the condition. aim of the study to investigate whether mean platelet volume, C-reactive protein, and hyperbilirubinemia can be used as inflammatory markers for the diagnosis of acute appendicitis and its correlation with histopathological examination. Methods: we prospectively analyzed 60 patients who were full fulling the inclusion criteria patients analysed for CBC, LFT and CRP and underwent for appendicectomy (Laparoscopic/open). Per-operative diagnosis was confirmed by histopathological examination from November 2020 to November 2022. Results: patients with CRP level > 6 and hyperbilirubinemia patients most likely to have acute appendicitis. Mean CRP level was 13.21±4.0 and mean bilirubin level 1.04±0.29 in case of acute appendicitis. CRP, hyperbilirubinemia levels were significantly higher in cases of acute appendicitis (p<0.01) while MPV value was not found significant. All patients was confirmed with histopathology examination. Conclusions: Serum bilirubin level and CRP estimation, which is a simple, cheap, and easily available laboratory test, can be added to the routine investigations in the diagnosis and severity of acute appendicitis and help in decreasing negative appendicectomy rates, especially in low modified Alvarado score.